The importance of impulse oscillometry in bronchial provocation testing in confirming the diagnosis of asthma in male army recruits - Koruga, Dragan Borislav; Tot Vereš, Kristina; Plavec, Goran; Lončarević, Olivera (Vojnosanitetski pregled, 2017)
Background/Aim. Impulse oscillometry (IOS) is a technique valid for measuring the lung function in obstructive lung diseases and bronchial provocation tests. However, no consensus exists for its use. The aim of the study was to assess impulse oscillometry sensitivity for detection of early airways changes during bronchial provocation testing and to compare with changes obtained with spirometry and bodyplethysmography in male army recruits. Methods. Male military recruits were submitted to bronchial provocation test with histamine by the aerosol provocation system. Out of 52 male military recruits subjected to attempts to make the diagnosis of asthma the study included 31 subjects with fall of forced expiratory volume in one second (FEV1) above 20%. The changes of impulse oscillometry were measured one step before and after provocation dose (PD) of histamine and compared with the changes of bodyplethysmography and spirometry. Results. The average age of male army recruits was 23.3 year. After bronchoprovocation there was an average increase of the total resistance at 5 Hz (R5) by 66.6%, resonant frequency (Fres) by 102.2%, Goldman index (AX) by 912.1%, the arway resistance (Raw) by 121.5%, and a decrease in reactance at 5 Hz (X5) by 132.1% and FEV1 by 25.6%. One step before the last inhaled of PD20 there was an average increase of 26.7% in R5, 24.1% in Fres, 85.3% in AX, 11.9% in Raw and a decrease in X5 by 26.9% and FEV1 by 4.3%. A correlation between impulse oscillometry and bodyplethysmography parameters was obtained. Conclusion. This paper demonstrates a sufficient sensitivity of impulse oscillometry to detect changes in airways, so it may play a complementary role in the diagnosis of asthma in male military recruits.
Keywords: asthma; diagnosis; bronchial provocation tests; histamine; respiratory function tests; sensitivity and specificity; military personnel; men; personnel selection